Multifunctional Dielectric Layers for the Fabrication of Ultra-Simplified n-PERT c-Si Solar Cells. (August 2016) - Cabal, Raphaël; Blévin, Thomas; Monna, Rémi; Veschetti, Yannick; Dubois, Sébastien
Abstract: Bifacial solar cell n-PERT concept involves boron and phosphorus doped regions requiring both proper surface passivation. In order to reduce n-PERT technology related €/W, one way considered is to simplify cell process-flow. In order to do so, we developed passivating/ anti-reflective/ doping SiOx Ny :B and SiNx :P layers. The co-anneal of these multifunctional layers allows for (1) emitter & BSF formation, (2) subsequent doped regions passivation, (3) providing satisfying optical properties. The features of our multifunctional PECV-deposited layers are detailed. By exploiting the passivating properties of our multifunctional layers we eventually present our so-called "SOLENNA(3 )" technology. This ultimately simplified technology provides large area (243cm 2 ) LID-free 19.8% efficient n-PERT cells with only 7 processing steps. This is to the authors' knowledge the simplest n-PERT process ever introduced with such a high level of performance. Finally, the cost calculation based on a 100MW line capacity and confronting SOLENNA(3) to referent technologies was completed. Due to its simplicity, it was shown that SOLENNA(3) technology can compete with the classical Al-BSF technology in terms of cost per watt at the module level.